Pengembangan Media Pembelajaran Kimia Berbasis Android Pada Materi Termokimia Kelas XI SMA - A'in Donasari; Ramlan Silaban (Universitas Negeri Medan, 2021)
The aim of this research was to know the feasibility and student learning outcomes of chemistry learning media based on android. This research is a type of research and development which is adapted from the ADDIE Analysis, Design, Development Implementation model. The media developed was tested on 30 students of class XI IPA RK Serdang Murni Lubuk Pakam Private High School. The data was collected through the expert validation sheet of student learning outcomes. The data analysis technique used quantitative and qualitative data analysis. The results of the research and the development concluded that: (1) Android-based chemistry learning media for class XI IPA students in this thermochemical material was developed with a 4D model and designed in the form of an application in the form of an android studio with the java programming language. (2) Android-based chemistry learning media for class XI Senior high school’s students have been declared eligible (valid) to be used in thermochemical learning. Eligibility (validity) of Android-based chemistry learning media for high school students of class XI, is found qualitatively based on the evaluation of material expert validators and media experts in terms of the feasibility of content, presentation, language and graphics according to BSNP with a mean of 4.04. (3) Based on the learning outcomes of students who are taught using Android-based chemistry learning media, it is not the same with the KKM value (75) based on the obtained mean of 90.17 with the highest value of 100 and the lowest score of 80.Thus, Android-based chemistry learning media in thermochemical is suitable for school use.